Study on antimicrobial and antioxidant activities Of male flowers (inflorescences) of Borassus flabellifer linn - F. GRICILDA SHOBA,; J. JOICE DEVAPRIYA,; J. SATHYA,; G. VIMALA, (International Journal of Pharma and Bio Sciences, 2017)
An antimicrobial and antioxidant activity of ethanol male flowers extract of Borassus flabellifer was evaluated by using DPPH scavenging and Minimum inhibitory concentration MIC test. For antibacterial activity, the bacterial species such as Klebsiella pneumoniae, Vibrio cholerae, Shigella dysenteriae, Escherichia coli and Staphylococcus aureus were tested in different concentrations of flower extract. The fungi species Candida albicans, Aspergillus niger and Aspergillus flavus were tested for antifungal activity. The results obtained for the present study showed that the plant has significant inhibition activity against all the tested bacteria and fungi. Among these, the bacterial species E. coli and fungal species C. albicans exhibited maximum level of inhibition such as 11mm and 13mm at 1000µg/ml of ethanol extract. From these results, it is concluded that the flower extract proved as a potential antimicrobial agent. The extract showed high antioxidant activity when compared to the standard drug vitamin E. The IC50 value of the extract was 213.3µg/ml. However, the extract possesses potential antimicrobial agent and a strong radical scavenger.